Development of a high-throughput SARS-CoV-2 antibody testing pathway using dried blood spot specimens. (March 2021) - Moat, Stuart J; Zelek, Wioleta M; Carne, Emily; Ponsford, Mark J; Bramhall, Kathryn; Jones, Sara; El-Shanawany, Tariq; Wise, Matt P; Thomas, Annette; George, Chloe; Fegan, Christopher; Steven, Rachael; et al.
Background: Serological assays for Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) have roles in seroepidemiology, convalescent plasma-testing, antibody durability and vaccine studies. Currently, SARS-CoV-2 serology is performed using serum/plasma collected by venepuncture. Dried blood spot (DBS) testing offers significant advantages as it is minimally invasive, avoids venepuncture with specimens being mailed to the laboratory. Methods: A pathway utilizing a newborn screening laboratory infrastructure was developed using an enzyme-linked immunosorbent assay to detect IgG antibodies against the receptor-binding domain of the SARS-CoV-2 spike protein in DBS specimens. Paired plasma and DBS specimens from SARS-CoV-2 antibody-positive and -negative subjects and polymerase chain reaction positive subjects were tested. DBS specimen stability, effect of blood volume and punch location were also evaluated. Results: DBS specimens from antibody-negative ( n = 85) and -positive ( n = 35) subjects and polymerase chain reaction positive subjects ( n = 11) had a mean (SD; range) optical density (OD) of 0.14 (0.046; 0.03–0.27), 0.98 (0.41; 0.31–1.64) and 1.12 (0.37; 0.49–1.54), respectively. An action value OD >0.28 correctly assigned all cases. The weighted Deming regression for comparison of the DBS and the plasma assay yielded: y = 0.004041 + 1.005 x, r = 0.991, Sy/ x 0.171, n = 82. Extraction efficiency of antibodies from DBS specimens was >99%. DBS specimens were stable for at least 28 days at ambient room temperature and humidity. Conclusions: SARS-CoV-2 IgG receptor-binding domain antibodies can be reliably detected in DBS specimens. DBS serological testing offers lower costs than either point of care or serum/plasma assays that require patient travel, phlebotomy and hospital/clinic resources; the development of a DBS assay may be particularly important for resource poor settings.